Covariates streamline age‐specific early life survival estimates of two chelonian species. (6th July 2018) - Arsovski, D.; Olivier, A.; Bonnet, X.; Drilholle, S.; Tomović, L.; Béchet, A.; Golubović, A.; Besnard, A.
Abstract: Delayed maturity and high survival rates of immatures and adults characterize long‐lived species' life histories. Understanding how these traits interact in stochastic environments is essential to understand early life in long‐lived species and to assist conservation planning. Unfortunately, available information of demographic traits in immatures are often fragmentary and the logistical difficulties of capturing and recapturing this cohort leave little room for improvement. Published immature chelonian survival estimates vary broadly, are often not age‐specific, and lack precision. In an attempt to overcome this issue, we developed a novel modelling approach based on Capture‐Recapture data to obtain robust age‐specific survival probabilities in two chelonian species (the freshwater European pond turtle, Emys orbicularis, and the terrestrial Hermann's tortoise, Testudo hermanni ). More specifically, we show that implementing a linear relationship between survival probabilities and age does not distort survival estimates and improves precision. Both species display a progressive increase in survival with age, reaching a plateau at the ages of four to five. As maturity occurs later in both species (8–12 years‐old), the survival plateau might be governed by the final hardening of the carapace, which brings obvious survival benefits. Taking advantage of the flexibility of multievent models we encourage a systematic field approach even when very large samples from immatures cannot be amassed. Only so can demographic traits in chelonians, and more generally in long‐lived species, be properly explored. Abstract : The elusive nature of immature animals with delayed maturity has hindered the estimation of age‐specific survival. Early life capture‐recapture datasets are often sparse and incomplete precluding precision. In order to ameliorate this circumstance, we present here a novel statistical approach that can help streamline results of age‐specific early life survival of two chelonian species. Such endeavors are crucial for proper construction of projection matrices, indispensable to ecological and evolutionary studies and efficient conservation planning.